2022
DOI: 10.3390/biomedicines10082051
|View full text |Cite
|
Sign up to set email alerts
|

Hashimoto’s Thyroiditis Minimizes Lymph Node Metastasis in BRAF Mutant Papillary Thyroid Carcinomas

Abstract: Hashimoto’s thyroiditis (HT) (autoimmune thyroiditis) is a clinicopathological entity associated with chronic lymphocytic infiltration resulting in hypothyroidism. HT is a double-edged sword that increases the risk of papillary thyroid cancer (PTC), yet it serves as a protective factor for PTC progression. BRAF mutation in PTCs is associated with rapid cell growth, aggressive tumor characteristics, and higher mortality rates. Here, we aimed to analyze the influence of HT in patients with PTCs and its effect on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Numerous works have found BRAF V600E mutation to be associated with a worse initial presentation [ 49 , 50 ]. Our results found that tumors with BRAF V600E mutation were almost twice as likely (RR = 1.79) as those with BRAF wild-type PTMC to develop ETE.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous works have found BRAF V600E mutation to be associated with a worse initial presentation [ 49 , 50 ]. Our results found that tumors with BRAF V600E mutation were almost twice as likely (RR = 1.79) as those with BRAF wild-type PTMC to develop ETE.…”
Section: Discussionmentioning
confidence: 99%
“… 43 In addition, BRAF V600E mutation was associated with lymph node metastasis of PTMC, however the proportion of lymph node metastasis in PTMC patients with BRAF V600E mutation and Hashimoto’s thyroiditis is significantly reduced. 44 Moreover, BRAF V600E mutation was not associated with lymph node metastasis of PTMC. 45–48 Younger age (<55 years old) was an independent risk factor for lymph node metastasis in PTMC in this study.…”
Section: Discussionmentioning
confidence: 92%
“…HT is the most common reason for hypothyroidism and is an autoimmune disease associated with chronic inflammation. Though works have suggested BRAF mutation as a risk factor for tumor aggressiveness and HT as a protective factor against tumor aggressiveness, few works have investigated the two simultaneously [ 11 , 17 ]. One potential explanation for the protective effect of HT, however, is the increased medical attention these patients already receive, and consequently, the detection of carcinomas earlier.…”
Section: Discussionmentioning
confidence: 99%